2014
DOI: 10.1039/c4ob01788a
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Michael addition–lactonisation of carboxylic acids using α,β-unsaturated trichloromethyl ketones as α,β-unsaturated ester equivalents

Abstract: Isothiourea HBTM-2.1 catalyses the Michael addition-lactonisation of 2-aryl and 2-alkenylacetic acids and α,β-unsaturated trichloromethyl ketones. Ring-opening of the resulting dihydropyranones and subsequent alcoholysis of the CCl3 ketone with an excess of methanol gives a range of diesters in high diastereo- and enantioselectivity (up to 95 : 5 dr and >99% ee). Sequential addition of two different nucleophiles to a dihydropyranone gives the corresponding differentially substituted diacid derivative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…In this case HyperBTM ( 9 ) was employed to activate several arylacetic acids to give trans lactones with excellent levels of selectivity (Scheme ). The same group demonstrated that a similar intermolecular process was also possible with trifluoromethylenones, trichloromethylenones and α‐ketophosphonates …”
Section: Itu‐catalyzed Reactions Involving Chiral Acylisothiouronimentioning
confidence: 88%
“…In this case HyperBTM ( 9 ) was employed to activate several arylacetic acids to give trans lactones with excellent levels of selectivity (Scheme ). The same group demonstrated that a similar intermolecular process was also possible with trifluoromethylenones, trichloromethylenones and α‐ketophosphonates …”
Section: Itu‐catalyzed Reactions Involving Chiral Acylisothiouronimentioning
confidence: 88%
“…Notably,t he 2substitution pattern frequently provides reduced stereoselectivity in related isothiourea-catalyzed methods. [30] b 2 -Amino esters 24 and 25 with 1-and 2-naphthyl substituents were readily prepared, as was heteroaromatic 2-thienyl 26.Beyond aryl acetic acid derivatives,t he use of (E)-pent-3-enoic acid pentafluorophenyl ester was also productive,p roviding 3alkenyl-substituted b 2 -amino ester 27 in excellent er. The consistent yield and enantiocontrol observed with variation in both steric and electronic aryl substitution within the ester component indicate that neither provide as ignificant bias in this process.F urther investigations probed the effect of Nsubstituents within the hemiaminal ether reaction partner (Table 2B).…”
Section: Scope Limitations and Synthetic Applicationsmentioning
confidence: 99%
“…The enolate was also utilized in intermolecular Michael‐addition‐catalyst elimination cascade sequence in combination with different types of suitable Michael acceptors in course of preparing several cyclic molecules like substituted δ ‐lactones and lactams (Scheme 30). [ 35,36 ]…”
Section: Six Membered Heterocycle Formation By Formal and Concerted [mentioning
confidence: 99%